Improvement of Transient Stability Performance of Captive Power Plant During Islanding Condition - Utpal Goswami; Tapas Kumar Sengupta; Arabinda Das (Institute of Advanced Engineering and Science, 2014)
This paper deals with an idea to improve the transient stability of captive generator sets during islanding condition. But doing so, the transient stability of the generator sets and the power system is severely disturbed in case of a fault in the utility side. In case of fault, the own generation is isolated, synchronization is lost and finally the sets go in islanding mode of operation. As such sets are of small size (5-50 MWs), total load throw-off in utility side causes disturbance in the transient form. If disturbances are not recovered immediately in terms of turbine speed, voltage variation etc., the power supply will be unstable and process suffers. A remedial measure, for the case concerned, can be taken with the aid of a SVC during the tripping of the utility load, at the generator bus before the frequency and voltage stabilization. The analysis was done using ETAP software.